Editorial Team - Rodríguez González, Sara (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2019)
EDITORS IN CHIEF EDITORIAL ASSISTANT ASSOCIATE EDITORS SCIENTIFIC COMMITTEE